Sustaining Tenancies or Swift Evictions: Rent Arrears in the Tenancy Tribunal - Toy-Cronin, Bridgette; Bierre, Sarah (Victoria University of Wellington Law Review, 2022)
There is a contradiction at the centre of tenancy practice and policy. On the one hand is the goal of sustaining tenancies to prevent homelessness and, on the other, a tribunal system for resolving tenancy disputes which is founded on achieving a "swift eviction". We analyse observations of tribunal hearings and mediations along with a sample of written orders. We ask whether the goal of sustaining tenancies can be achieved in a legislative framework originally intended to achieve swift eviction. We find that mediation creates space for determining a plan to pay off arrears but with little assurance the payments are accurate and realistic. Tribunal hearings for rent arrears allow limited discretion for continuing the tenancy, but even this discretion is restricted in practice. We conclude that there is a need to shift from "swift eviction" to recognising rent arrears as a consequence of poverty – one that requires support and intervention. While legislative change would support this shift, there is scope for significant improvement via process changes that borrow from the problem-solving approach of Te Ao Mārama.